The skills necessary for work place: Accounting graduates’ perceptions - Mohd Hanefah, Mustafa; Ismail, Samehah (MCB UP Ltd, 2003)

(untitled)
Many researchers have debated the relevance of accounting curriculum to the employers in the U.S. and other developed countries. Accounting graduates are said to lack various skills that are important in today's job market. Among them are technological skills, oral and communication skills, and professional skills.This phenomenon is not only common in developed countries, but also in the developing countries like Malaysia. In Malaysia, graduates from local universities and colleges are facing unemployment due to the lack of such skills. Although the Malaysian economy is performing better than other countries in this region, yet the unemployment rate among graduates is still high. The main objective of this research is to study the perceptions of the Malaysian graduates toward professional and technological skills that are vital for accounting graduates. The results indicate that a majority of the respondents strongly perceived that accounting curriculum should give high priority to certain professional and technological skills. This include: English language, analytical/critical thinking, business decision modelling, interpersonal, negotiation, teamwork, oral and written communication, and risk analysis.Professional skills that were perceived to be important by the respondents include: accounting software, communication software, database software, electronic commerce, file and directory management, information systems planning and auditing, presentation software, spreadsheet, technology security and control,windows, word processing software, and worldwide web tools. Based on the findings implications for accounting education are also discussed.